Directly Coating Hydrogel on Filter Paper for Effective Oil–Water Separation in Highly Acidic, Alkaline, and Salty Environment. (27th July 2015) - Fan, Jun‐Bing; Song, Yongyang; Wang, Shutao; Meng, Jingxin; Yang, Gao; Guo, Xinglin; Feng, Lin; Jiang, Lei
Abstract : The separation of oil–water mixtures in highly acidic, alkaline, and salty environment remains a great challenge. Simple, low‐cost, efficient, eco‐friendly, and easily scale‐up processes for the fabrication of novel materials to effective oil–water separation in highly acidic, alkaline, and salty environment, are urgently desired. Here, a facile approach is reported for the fabrication of stable hydrogel‐coated filter paper which not only can separate oil–water mixture in highly acidic, alkaline, and salty environment, but also separate surfactant‐stabilized emulsion. The hydrogel‐coated filter paper is fabricated by smartly crosslinking filter paper with hydrophilic polyvinyl alcohol through a simple aldol condensation reaction with glutaraldehyde as a crosslinker. The resultant multiple crosslinked networks enable the hydrogel‐coated filter paper to tolerate high acid, alkali, and salt up to 8m H2 SO4, 10m NaOH, and saturated NaCl. It is shown that the hydrogel‐coated filter paper can separate oil–water mixtures in highly acidic, alkaline, and salty environment and oil‐in‐water emulsion environment, with high separation efficiency (>99%). Abstract : A exceedingly simple strategy for fabricating hydrogel coated filter paper having the capacity to resist highly acidic, alkaline and salty environment is demonstrated. The resulting multiple crosslinked networks enable the hydrogel coated filter paper to separate various oil‐water mixtures in a range of highly acidic, alkaline and salty environment with high separation efficiency.